Design And Build A Conventional Transaksi Payment System Using Cashless - Adhari, Lela; Shantika Sari, Yulia; Nugraha, Yopi; Tetep (RISTEC : Research in Information Systems and Technology, 2020)
Technology is developing at this time very rapidly, especially technology in smartphones, today's smartphones have become a basic need for society, the many innovations in smartphones provide convenience in work that can be done by humans. Including in terms of online transactions, many innovations have been made, including online payments, in this case, supermarkets. Some supermarkets have used technology in their business processes, but only some supermarkets have used these stores. The purpose of this research is to create an application that can record transactions that occur, as well as assist in managing the backend of the supermarket, such as managing data on goods, & employees. While the method of analysis carried out in this study is (literature from several journals and books, questionnaires, interviews also identify applications that are almost the same or similar), while the design method used is extreme programming. The result of this research is an online payment application with features such as a brief description of the store, information on items that are being promoted, view bill features, and bill request. The conclusion of this research is that it can help consumers pay for goods digitally even if not at minimarkets, as well as improve store performance for consumers by using good applications.